PERANAN ADVOKAT SEBAGAI KUASA HUKUM DALAM MENGHADIRKAN PARA PIHAK PADA PERKARA MEDIASI PERCERAIAN NOMOR: 300/PDT.G/2011/PA.PBR DI PENGADILAN AGAMA PEKANBARU - Nurkamilah '; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In completing the legal issues, the litigants will satisfy the demands of rights aims to obtain legal protection. Dispute resolution used by the parties one of which is through mediation is a way of solving the problem with the aim of reaching agreement between the parties with the assistance of a mediator. Implementation of mediation is also done in the Religious Court based civil judicial and justice of Islam in Indonesia. Stage reconciling the parties initially contained in Article 130 HIR / RBG 154, then the Supreme Court of the Supreme Court issued Regulation No. 1 Year 2016 About the Mediation Procedure in court. In resolving a dispute many parties choose to use services of lawyers because they feel it easier to solve the problems and enlightened law, but it should be noted that not all the stages of the settlement can be represented by an advocate. One of them is in the process of divorce mediation in the Religious, advocates can only assist the parties and is not allowed to represent the party as a whole in the implementation process of mediation. This is in accordance with Article 82 of Law No. 7 of 1989 About Jo Religious Courts Law No. 50 of 2009 Regarding the second amendment to Law No. 7 of 1989 About the Religious CourtsI researched this research establishes key issues about how the role of lawyers as legal counsel in mediating a divorce case in the Religious Court of Pekanbaru and how the effort and the legal consequences within the constraints faced by lawyers in the case of divorce mediation divorce Number: 300 / Pdt.G / 2011 / PA .PBR Religious Court of Pekanbaru.The method used in this research is a kind of sociological research is the research field to see the effectiveness of the law. While the nature of the research that I use is explorative which aims to deepen the knowledge about the symptoms of the law on "the role of lawyers as legal counsel in bringing the parties to the divorce mediation cases Number: 300 / PDT.G / 2011 / PA.PBR Religious Court of Pekanbaru" , From the research that I researched that the role of lawyers as legal counsel in mediating a divorce case in the Religious Court of Pekanbaru is to provide legal understanding of how the judicial procedure in the Religious Court. advocates further efforts made in the face of constraints on divorce mediation cases Number: 300 / PDT.G / 2011 / PA.PBR Religious Court of Pekanbaru is to give the judge announcing a call addressed to the applicant to be present directly in carrying out mediation.Keywords: Role of Advocates - Mediation - Religious Court